CORPORATE GOVERNANCE DAN NILAI PERUSAHAAN DENGAN INTERNET FINANCIAL REPORTING SEBAGAI VARIABEL INTERVENING - M. Riduan Abdillah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, The purpose of this research examines the influence of corporate governance on corporate value with Internet Financial Reporting (IFR) as an intervening variable.This research is based on agency theory proposed by Jensen and Meckling (1976) that between agent (management) and principal (shareholders) there will always be information asymmetry and trigger agency cost. The independent variable of corporate governance is measured by Corporate Governance Index (CGI) (Siagian et.al 2013), intervening variable is Internet Financial Reporting (IFR) measured by Internet Disclosure Index (IDI) (Spanos and Mylonakis, 2006; Puspitaningrum and Atmini, 2012 ) and the dependent variable is firm value measured by price to book value (Siagian et.al 2013) and control variable that is firm size measured by natural total logarithm of company asset (Puspitaningrum and Atmini, 2012; Siagian, et al.2013). The research population is all manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2016. The sample research using purposive sampling method. Statistical test tool uses path analysis. The results show that corporate governance directly affects the value of the company. However, the results of the testing of this study can not prove that Internet Financial Reporting (IFR) mediates the relationship between corporate governance on corporate value.